2012
DOI: 10.1177/1039856211432485
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension and companionship in the emergency department as predictors of treatment adherence

Abstract: This preliminary study suggests that ensuring patients' understanding of treatment recommendations and encouraging the company of patients are achievable, practical strategies that may improve adherence and thereby promote better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…As a result, the Australian indicates that hospitals that specifically support and train nurses to conduct effective clinical handovers may see a reduction in adverse events for patients Garling, 2009; Organisation for Economic Co-Operation & Development, 2011;Sabir, Yentis, & Holdcroft, 2006;World Health Organisation, 2014). When clinicians and patients communicate effectively, patients appear to have lower anxiety levels, better compliance with treatment plans, and more positive health outcomes, including a lower likelihood of being rehospitalized within 30 days of discharge (Ekwall, 2013;Jack et al, 2009;Nitzan et al, 2012).…”
Section: Background-communication At Handovermentioning
confidence: 99%
“…As a result, the Australian indicates that hospitals that specifically support and train nurses to conduct effective clinical handovers may see a reduction in adverse events for patients Garling, 2009; Organisation for Economic Co-Operation & Development, 2011;Sabir, Yentis, & Holdcroft, 2006;World Health Organisation, 2014). When clinicians and patients communicate effectively, patients appear to have lower anxiety levels, better compliance with treatment plans, and more positive health outcomes, including a lower likelihood of being rehospitalized within 30 days of discharge (Ekwall, 2013;Jack et al, 2009;Nitzan et al, 2012).…”
Section: Background-communication At Handovermentioning
confidence: 99%
“…In particular, research has demonstrated the link between patient-centred communication and • greater levels of patient satisfaction (Ekwall 2013;McMillan et al 2013;Perez-Carceles et al 2010), • engagement in healthcare consultations (McMillan et al 2013), • comprehension and understanding of treatment procedures and diagnosis and • subsequent agreement with clinicians' recommended treatment regimens, and adherence to them (McMillan et al 2013;Nitzan et al 2012). In particular, research has demonstrated the link between patient-centred communication and • greater levels of patient satisfaction (Ekwall 2013;McMillan et al 2013;Perez-Carceles et al 2010), • engagement in healthcare consultations (McMillan et al 2013), • comprehension and understanding of treatment procedures and diagnosis and • subsequent agreement with clinicians' recommended treatment regimens, and adherence to them (McMillan et al 2013;Nitzan et al 2012).…”
Section: Patient-centred Carementioning
confidence: 99%
“…Benefits include greater rates of patient satisfaction (see, e.g. McMillan et al 2013;Nitzan et al 2012); and declines in rates of rehospitalisation (Clancy 2009;Jack et al 2009). Charmel and Frampton 2008;Lau 2000); higher levels of patient comprehension of diagnosis and treatment and subsequent adherence to hospital discharge or treatment instructions (see, e.g.…”
Section: Research On Patient Experience and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Department of Health, 2013). Patient-centered care has been correlated with greater levels of patient satisfaction with, and informed involvement and participation in, their treatment (Buckley et al, 2013; Nitzan et al, 2012; Rider et al, 2014; Slade et al, 2011). As Hobgood, Riviello, Jouriles, and Hamilton (2002) wrote, patient-centered care positions the “patient’s experience of the illness” on equal footing with the treatment of their health complaint or disease, and recognizes the development of rapport and empathy between patients and clinicians, through sustained interpersonal communication, as essential to securing effective patient–clinician alliances (p. 1258).…”
mentioning
confidence: 99%